Pengembangan Aplikasi Sistem Bimbingan Penasehat Akademik (PA) Jurusan Sistem Informasi Filkom UB Berbasis Mobile Native Android - Togan Jagat Raya; Herman Tolle; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Information Systems Department at the Faculty of Computer Science is one of the departments that has accreditation A at Brawijaya University. In order to provide quality education for its students, apart from providing academic knowledge, the Information Systems Department also provides guidance, motivation, and academic advice to students which is known as academic advisory guidance. Academic advisory guidance has been standardized according to the curriculum of the Information Systems Department, but this guidance is still carried out conventionally and manually, starting from collecting the forms, filling the forms, procedures for guidance, and obtaining the results. Therefore, with this application, the guidance of a fairly complex academic advisor can be done simply because in this application can processes some data automatically, such as the calculation of GPA and SKS, student GPA and SKS categories, and so on. This system is implemented on the Android platform. Blackbox test results produce 100% valid functionality. Whereas in usability testing, interface measurements are carried out to measure general user measurements of applications from 5 respondents, resulting in a total score of 72.5.